The emergency management of patients who have experienced sexual violence: an integrative literature review - Quiroga, Neil Dylan (University of the Witwatersrand, Johannesburg, 2023)
Background: Sexual violence is endemic in many countries, and particularly in South Africa.. Over the past few years there have been several advancements in the care for patients who have experienced sexual violence. However, the care available in resource limited settings and in South Africa, remains inconsistent and often inadequate. Purpose of the Study: To synthesize the current evidence based practice in the emergency management of patients who have experienced sexual violence; and to review which advancements could be feasible in a resource limited setting, and in the South African context. Methods: This study conducted an integrative literature review on the emergency management of patients who experience sexual assault, in order to synthesise the current literature. The research is structured on Whittemore and Knafl’s framework, and utilizes their five stages of an integrative review: problem identification, literature search, data evaluation, data analysis, and presentation. The following databases were searched: Cochrane library, EBSCOhost (CINAHL; ERIC and MEDLINE), PubMed, ScienceDirect, Wiley online library and Psycinfo. 2142 articles were assessed fully for eligibility, and a total of 47 articles were included in the integrative review. The literature search was conducted over a period of 4 months. Thematic analysis of the 47 articles was then conducted using MaxQDA (Qualitative Coding Software). A conductive coding approach was used, based on grounded theory. Results: Eight main themes, and thirty four subthemes, emerged from the data that spoke directly to the research question and objectives. The eight major themes were: Screening patients for sexual violence; emergency medical care for survivors; forensic care; mental health care; follow up care and services; technological aids to augment care; structural or organization aspects affecting care; and health care worker factors that affect care for survivors. Conclusion: The study strongly recommends integrating trauma informed care into every aspect of care for survivors of sexual violence in South Africa. The study also recommends implementing: screening of patients for various forms of sexual violence; quality improvement drivers such as order sets and clinical pathways; and nurse driven innovations in pro-active follow up services and new mental health care interventions
A research report submitted in partial fulfillment of the requirements for the Degree of Master of Science in Nursing to the Faculty of Health Sciences, School of Nursing, University of the Witwatersrand, Johannesburg 2023
Keywords: Emergency Care; Forensic Care; Psychological Care; Resource Limited Setting; UCTD; SDG-3: Good health and well-being